Why and how least developed countries can receive more FDI to meet their development goals - Ken Davies (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2011)
The 48 least-developed countries (LDCs), most of them in sub-Saharan Africa and a few in Asia, need foreign direct investment (FDI) to help meet their development targets. The FDI they now receive, although inadequate, is enough to demonstrate that investors see potential in them. It is therefore realistic for LDCs to seek more FDI, but they need to enhance their investment environments to attract it in the much greater quantities required. Donors can help by targeting official development assistance (ODA) on investment in human capital and supporting governance improvements. Meanwhile, LDCs should establish effective investment promotion agencies (IPAs).
Keywords: 330